2018
DOI: 10.1038/s41398-018-0279-3
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and neuroanatomical impairments associated with chronic exposure to levamisole-contaminated cocaine

Abstract: Currently, levamisole is the most common cocaine adulterant worldwide and it is known to induce a variety of adverse side effects. Animal studies and human case reports suggest potential neurotoxicity of the compound but neither neuroanatomical nor cognitive effects of levamisole have been systematically investigated in cocaine users so far. We examined cognitive performance and cortical structural differences between chronic cocaine users with low and high recent exposure to levamisole objectively determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 59 publications
(83 reference statements)
6
36
2
1
Order By: Relevance
“…In the present study, we aimed to reanalyze a previously published data set with respect to the long-term neurotoxic effects of levamisole-adulterated cocaine on white matter structures. 25 In a previous study, we showed that cocaine users with a high exposure to levamisole displayed reduced cortical thickness, specifically in the middle frontal gyrus, compared to controls and to cocaine users with low levamisole exposure. 25 In the present study, we also analyzed fluid attenuated inversion recovery (FLAIR) images, which were not reported in the previous study.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…In the present study, we aimed to reanalyze a previously published data set with respect to the long-term neurotoxic effects of levamisole-adulterated cocaine on white matter structures. 25 In a previous study, we showed that cocaine users with a high exposure to levamisole displayed reduced cortical thickness, specifically in the middle frontal gyrus, compared to controls and to cocaine users with low levamisole exposure. 25 In the present study, we also analyzed fluid attenuated inversion recovery (FLAIR) images, which were not reported in the previous study.…”
Section: Introductionmentioning
confidence: 81%
“…24 However, the dose-dependent effect of levamisole exposure on neurocognitive function and the thinning of distinct cortical areas in human cocaine users has been demonstrated only recently. 25 Although the mode of action of levamisole has yet to be fully elucidated, interaction with nicotinic acetylcholine receptors, stimulation of monoamine transmission and modulation of immune responses have been implicated. 17 Based on existing knowledge of levamisole's action on vessel function, it is likely to contribute to white matter damage in the human brain as well.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we did not control for the potential impact of adulterants such as levamisole. A recent study from our laboratory showed that levamisole-exposure was associated with alterations in fronto-cortical structures of CU ( Vonmoos et al, 2018 ). Unfortunately, in the present study levamisole was not determined in hair at baseline, thus, we were not able to analyze a possible relationship between changes in hair levamisole concentration and GM.…”
Section: Discussionmentioning
confidence: 99%
“…The Dutch drug monitoring system has observed an increase of up to >70% of cocaine adulterated with levamisole from 2006 to 2014. Levamisole is cheap, has similar physical properties as cocaine, and its metabolite (aminorex) has a longer half-life and amphetamine-like effects that can lengthen the effects of cocaine [6][7][8].…”
Section: Discussionmentioning
confidence: 99%